The The Utilization of Cocoa Pod Husk-Based Compost Inoculated with Arbuscular Mycorrhizal Fungi on Soil Chemical Properties and Nutrient Uptake of Coffee Plants - Perdana, Andrian; Puspita Sari, Niken; Zakariyya, Fakhrusy; Anita Sari, Indah; Astika Sari, Dini (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2025)
Sustainable waste management and the preservation of soil health represent critical challenges in intensive coffee and cocoa plantation. Composting offers an effective approach for sustainable waste management by enhancing soil health, while arbuscular mycorrhizal fungi (AMF) optimize nutrient uptake (NU) efficiencyin coffee plants. This research aimed to investigate the effect of cocoa pod huskbased compost inoculated with AMF on soil chemical properties and NU in coffee plants. This research employed a completely randomized design with two factors. Factor I consisted of three compost doses: K0 (no compost), K1 (15% compost,w/w), and K2 (30% compost, w/w). Factor II comprised three levels of AMF: F0 (no AMF), F1 (15 g polybag-1 ), and F2 (30 g polybag -1 ). Compost application significantly enhanced soil nutrient levels of N, P, K, C-organic, and CEC, as well as improved the uptake of N, P, and K by coffee plants. Similarly, AMF significantly increased soil P levels and P uptake by coffee plants. The combined application of compost and AMF further contributed to an increase in soil P availability. The K1F1 treatment (15% compost and 15 g AMF polybag -1 ) was the most effective in optimizing nutrient turnover, as indicated by the highest uptake of N (33.48 g plant -1) and P (1.37 g plant -1), which contributed to enhance plant performance. According to nutrient availability classification, this treatment supplied sufficient soil N (0.36%) and soil organic C (SOC) (2.54%). However, excessive N and SOC induces antagonistic interactions, compromising the efficient uptake of P and K, while deficiencies constrain overall nutrient acquisition.